Penerapan Algoritma Fp-Growth Dalam Menganalisis Pola Penjualan Produk Teh Untuk Menentukan Produk Unggulan Pada PT Kartini Teh Nasional - Amanata Yukha; Indrayanti; Risqiati (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
Abstract : This study applies the FP-Growth algorithm to analyze sales patterns and determine flagship products at PT Kartini Teh Nasional. The key problem is the underutilization of transaction data to understand consumer preferences and purchasing patterns. The research aims to develop an association-based data mining model to support marketing strategy and inventory management. The tea products analyzed and sold by the company include: Dandang 1T, Dandang 400gr, Dandang 1/4T, Dandang 2in1, Blacktea Box 25pcs, Jasmine Renceng 8pcs, Jasmine Pack 100pcs & Lunchbox, Blacktea Pack 100pcs, Blacktea Vanilla, Jasmine Box 25pcs, Ningrat Tea, and Blacktea Renceng 8pcs. FP-Growth analysis produces frequent itemsets and association rules, where the highest values are found in the best-selling product combinations: Dandang 1T (support 97.0%; confidence 97.0%), Dandang 2in1 (support 97.0%; confidence 97.0%), and Jasmine Renceng 8pcs (support 97.0%; confidence 98.5%). The highest confidence is held by Jasmine Renceng 8pcs at 98.5%, indicating the strongest purchase consistency in association patterns. Based on these results, the three products are identified as flagship items that can serve as a basis for promotional strategy, product bundling, and more efficient stock management. The FP-Growth algorithm proves effective in uncovering hidden purchasing patterns to enhance the company’s competitive advantage.